2016
DOI: 10.1016/j.clinph.2015.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial sleep deprivation on slow waves during non-rapid eye movement sleep: A high density EEG investigation

Abstract: Objective Changes in slow waves during non-rapid eye movement (NREM) sleep in response to acute total sleep deprivation are well-established measures of sleep homeostasis. This investigation utilized high-density electroencephalography (hdEEG) to examine topographic changes in slow waves during repeated partial sleep deprivation. Methods Twenty-four participants underwent a 6-day sleep restriction protocol. Spectral and period-amplitude analyses of sleep hdEEG data were used to examine changes in slow wave e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 44 publications
1
31
1
Order By: Relevance
“…However, at first glance, it seems counterintuitive that pharmacological sleep induction and sleep restriction by gentle handling would result in similar improvements. Based on these results and previous findings (Vienne et al, 2010, Bellesi et al, 2013, Hodor et al, 2015, Plante et al, 2015, we then hypothesized that both conditions might produce deeper sleep; that is, increased delta power. In fact, we found that SI animals spent more time in SWS compared with the control group.…”
Section: Discussionmentioning
confidence: 52%
“…However, at first glance, it seems counterintuitive that pharmacological sleep induction and sleep restriction by gentle handling would result in similar improvements. Based on these results and previous findings (Vienne et al, 2010, Bellesi et al, 2013, Hodor et al, 2015, Plante et al, 2015, we then hypothesized that both conditions might produce deeper sleep; that is, increased delta power. In fact, we found that SI animals spent more time in SWS compared with the control group.…”
Section: Discussionmentioning
confidence: 52%
“…Over the last 2 decades, the use of high-density EEG and sleep neuroimaging methods has steadily increased in both healthy and clinical populations [64][65][66][67]. Both approaches have further refined our understanding of the localized and neural underpinnings of healthy and disrupted sleep, as well as of circadian variations in brain functions [68][69][70].…”
Section: Advanced Sleep Measurement Methodsmentioning
confidence: 99%
“…In these studies, sleep opportunity was 4 hr per night [14][15][16], 5 hr per night [17], and 4, 6, or 8 hr per night [5], and in most of these experiments, a homeostatic response in SWA was observed. The response to sleep restriction stabilizes quickly [5,18], which is in accordance with the exponential parameters of the homeostatic process in the two-process model.…”
Section: Introductionmentioning
confidence: 93%
“…To obtain a fair comparison between different conditions [16,17], SWA was averaged over the first 331 30 s epochs of NREM sleep (2.8 hr, i.e. the maximum number of NREM sleep epochs common to all nights; see Methods).…”
Section: Swa In the First 331 Epochs Of Nrem Sleepmentioning
confidence: 99%
See 1 more Smart Citation